Understanding the effect of carbon nanotube functionalization on copper electrodeposition - Ewa Kazimierska (Journal of Applied Electrochemistry, 2019)
The dynamics of electrochemical deposition and dissolution of copper in the presence of functionalized multiwalled carbon nanotubes in solution has been studied in detail using an electrochemical quartz crystal microbalance. Results demonstrate the central role of carbon nanotube functionalization on the values of mass and current densities of copper deposition. Amine functionalization increases competitive hydrogen evolution without significantly affecting the total amount of deposited copper, whereas carboxylic functionalization clearly enhances the deposition of larger amounts of smoother copper deposits. Molar mass analysis of deposited species reveals interactions of carbon nanotubes with the electrode surface dependent on the type of functionalization. The effect of carbon nanotube functionalization should be closely considered in the development of electrochemical strategies for the integration of carbon nanotubes in metallic copper.